Prolonged circulation and increased tumor accumulation of liposomal vincristine in a mouse model of rhabdomyosarcoma. (May 2017) - Roveri, Maurizio; Pfohl, Alice; Jaaks, Patricia; Alijaj, Nagjie; Leroux, Jean-Christophe; Luciani, Paola; Bernasconi, Michele
Aim: Our goal was to improve vincristine (VCR) based rhabdomyosarcoma (RMS) therapy by encapsulating the drug into liposomes. A targeting strategy was attempted to enhance tumor accumulation.Materials & methods: VCR was loaded in control and peptide-decorated liposomes via an active method. The interaction of an RMS-specific peptide with the presumed target furin and the cellular uptake of both liposomal groups were studied in vitro . Pharmacokinetics and biodistribution of VCR-containing liposomes were assessed in an RMS xenograft mouse model.Results: Liposomes ensured high VCR concentration in plasma and in the tumor. Peptide-decorated liposomes showed modest uptake in RMS cells.Conclusion: The investigated peptide-modified liposomal formulation may not be optimal for furin-mediated RMS targeting. Nevertheless, VCR-loaded liposomes could serve as a delivery platform for experimental RMS.